Shooting Polaris : a personal survey in the American West - Hales, John, 1952- (University of Missouri Press, 2005)
"Memoir of surveying for the BLM in the Utah Desert. Reflects on man's relationship to nature and work, the Mormon Church and the settling of the West, the idealistic legacy of the sixties, the controversy over Glen Canyon Dam, and the often antagonistic relationship of American capitalism to ecological management"--Provided by publisher